The Effect of Profitability, Asset Growth, and Profit Growth on Company Value : An Empirical Study of the Technology Sector Listed on the IDX for the 2021-2024 Period - Natalia Pasaribu; Dadang Irawan; Sigit Pramono Hadi (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study is to examine the influence of profitability, asset growth, and profit growth on firm value in technology sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research population includes 47 technology companies, from which 9 companies were selected using a purposive sampling technique to meet the study criteria. This research applies a quantitative approach with multiple linear regression analysis to test the hypotheses. Data analysis includes descriptive statistics, classical assumption tests, and hypothesis testing using t-tests and F-tests. The results of the partial test (t-test) indicate that profitability and profit growth have a positive and significant effect on firm value, demonstrating that higher profitability and sustained profit growth increase investors’ confidence, which leads to improved valuation. Conversely, asset growth does not significantly influence firm value, suggesting that an increase in assets does not necessarily reflect better performance or market perception in the technology sector. The simultaneous test (F-test) produces an F-value of 10.203 with a significance level of 0.000, confirming that profitability, asset growth, and profit growth collectively exert a significant effect on firm value. Furthermore, the coefficient of determination (R²) is 0.489, meaning that 48.9% of the variation in firm value is explained by these three independent variables, while the remaining 51.1% is influenced by other factors not included in this model. These findings imply that firms should prioritize profitability and profit growth strategies to enhance their market value in the competitive technology industry.